A Case Report: Rapid Micro‐Induction of Buprenorphine/Naloxone to Administer Buprenorphine Extended‐Release in an Adolescent With Severe Opioid Use Disorder. Issue 6 (29th April 2020) - Azar, Pouya; Wong, James S.H.; Jassemi, Sara; Moore, Eva; Vo, Dzung X.; Nikoo, Mohammadali; Young, Samantha
Abstract : Background and Objectives: Buprenorphine extended‐release (BUP‐XR) is a monthly injectable form of opioid agonist therapy. Before its administration, a minimum 7‐day induction period with a transmucosal buprenorphine‐containing product is recommended. Methods: Case report ( n  = 1). Results: A 16‐year‐old female with active, severe opioid use disorder (OUD) and stimulant use disorder, hepatitis C virus, co‐occurring mental health disorders, and complex social stressors had five recent overdoses requiring naloxone. She had previously been treated with methadone and several trials of sublingual buprenorphine/naloxone, but would quickly discontinue the treatment. Using a rapid micro‐induction protocol, buprenorphine/naloxone was administered for 3 days. On day 4, 300 mg BUP‐XR was administered subcutaneously. Minimal withdrawal symptoms occurred, despite recent fentanyl use. Discussion and Conclusions: A rapid sublingual buprenorphine/naloxone micro‐induction was successfully used to initiate BUP‐XR, thereby eliminating the abstinence period prior to buprenorphine/naloxone administration, shortening the induction period, and minimizing withdrawal. Scientific Significance: This is the first reported case of using rapid micro‐induction as a bridge to initiate BUP‐XR. By reducing the length of induction to 4 days and minimizing withdrawal, this induction method can make BUP‐XR more accessible to patients who would otherwise refuse the medication due to concerns of enduring withdrawal. (Am J Addict 2020;29:531–535)